“DIILA O’ONTO BO WOLU-WOLUWO” (POTRET DISTRIBUSI KEUNTUNGAN OLEH PEDAGANG DI WARUNG MAKAN GORONTALO) - Mohamad Anwar Thalib; Nurahmi Tiara; Miftahur Rizkah; Sulis Lia Syamsudin (RISTANSI: Riset Akuntansi, 2022)
This study aims to reveal the use of profits by food stall entrepreneurs in Gorontalo. The informant determination technique used in this research is purposive sampling. The informants in this research are three food stall entrepreneurs. The type of method used in this research is qualitative. The results show that restaurant traders used a portion of the profits they earned for charitable activities such as giving alms, sharing food, and free basic necessities. The conclusion of this research is that traders use/distribute profits from selling not only to fulfill personal interests, but also to do charity in the form of helping people in need. In the culture of the Gorontalo people, parents (the elders) often give advice about these charitable activities through the expression diila o'onto bo wolu-woluwo/invisible but present. This research provides benefits regarding the presence of the concept of profit accounting based on the value of local wisdom of the Gorontalo community.